Using exome sequencing to decipher family history in a healthy individual: Comparison of pathogenic and population MTM1 variants. Issue 5 (25th July 2018) - Penon, Monica; Zahed, Hengameh; Berger, Victoria; Su, Irene; Shieh, Joseph T.
Abstract: Background: When a family encounters the loss of a child early in life, extensive genetic testing of the affected neonate is sometimes not performed or not possible. However, the increasing availability of genomic sequencing may allow for direct application to families in cases where there is a condition inherited from parental gene(s). When neonatal testing is not possible, it is feasible to perform family testing as long as there is optimal interpretation of the genomic information. Here, we present an example of a healthy adult woman with a history of recurrent male neonatal losses due to severe respiratory distress who presented to Medical Genetics for evaluation. A family history of additional male neonatal loss was present, suggesting a potential inherited genetic etiology. Methods: Although there was no DNA available from the neonates, by performing exome sequencing on the healthy adult woman, we found a missense variant in MTM1 as a potential candidate, which was deemed pathogenic based on multiple criteria including past report. Results: By performing an analysis of all known MTM1 ‐disease associated mutations and control population variation, we can also better infer the effects of missense variations on MTM1, as not all variants are truncating. MTM1 ‐X‐linked myotubular myopathy is a condition that leads to male perinatal respiratory failure and a high risk for early mortality. Conclusions: The application of genetic testing in the healthy population here highlights the broader utility of genomic sequencing in evaluating unexplained recurrent neonatal loss, especially when genetic testing is not available on the affected neonates. Abstract : Broad genomic testing is increasingly being considered for even healthy individuals, as it can be useful for people with a family history of a serious medical condition. Here, with unexplained neonatal loss, testing of parent/family member DNA was utilized to determine a genetic condition carried in the family. Bioinformatic and structural comparison of pathogenic and population MTM1 variants reveal patterns in missense variants (missense depletion and concentration) that help us understand X‐linked myotubular myopathy.